If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(2x + -2) = (2x + 7)(x + -1) Reorder the terms: x(-2 + 2x) = (2x + 7)(x + -1) (-2 * x + 2x * x) = (2x + 7)(x + -1) (-2x + 2x2) = (2x + 7)(x + -1) Reorder the terms: -2x + 2x2 = (7 + 2x)(x + -1) Reorder the terms: -2x + 2x2 = (7 + 2x)(-1 + x) Multiply (7 + 2x) * (-1 + x) -2x + 2x2 = (7(-1 + x) + 2x * (-1 + x)) -2x + 2x2 = ((-1 * 7 + x * 7) + 2x * (-1 + x)) -2x + 2x2 = ((-7 + 7x) + 2x * (-1 + x)) -2x + 2x2 = (-7 + 7x + (-1 * 2x + x * 2x)) -2x + 2x2 = (-7 + 7x + (-2x + 2x2)) Combine like terms: 7x + -2x = 5x -2x + 2x2 = (-7 + 5x + 2x2) Add '-2x2' to each side of the equation. -2x + 2x2 + -2x2 = -7 + 5x + 2x2 + -2x2 Combine like terms: 2x2 + -2x2 = 0 -2x + 0 = -7 + 5x + 2x2 + -2x2 -2x = -7 + 5x + 2x2 + -2x2 Combine like terms: 2x2 + -2x2 = 0 -2x = -7 + 5x + 0 -2x = -7 + 5x Solving -2x = -7 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -2x + -5x = -7 + 5x + -5x Combine like terms: -2x + -5x = -7x -7x = -7 + 5x + -5x Combine like terms: 5x + -5x = 0 -7x = -7 + 0 -7x = -7 Divide each side by '-7'. x = 1 Simplifying x = 1
| 28x+21=42x+14 | | 175m-125m+43200=45450-175m | | (-2x+4)(5x-6)= | | (3m^-3/2n^-2)^-3 | | 6x^3-33x^2+45x=0 | | (7-2)p=5-8 | | 1/3g+4=2 | | 2/7p+8=1/2p+5 | | 23=9+7x | | 3x+53=8-2x | | 5x+3-4x=-7 | | xsquared+px-q=0 | | 25c=2c-9 | | 9+x+5=44-x | | 24/36=2/x | | 10b+7= | | 3y-x=180 | | 5x+12-3x=8x+3 | | 2y+x=90 | | d/dx=x^3 | | d/dxx^2/3 | | 9x-2=6+8x | | (4x+5)^4/5=81 | | 60=-2x-2x+6(x+10) | | 42=7+z/5 | | -64=-4(n-5) | | 2(x+5)+3(x-10)=100 | | 2x-4(x+3)-10=6 | | -(2x+8)=-20 | | x-7=.5x | | -6(n+4)=30 | | 5b+12-2b+6=-15 |